الصلح الإداري لدى إدارة الحفظ العقاري - قديري، الطيب Qadiri, Altayeb (جامعة ابن خلدون تيارت, 2018)
The Algerian legislator has organized the administrative reform of the Directorate of Real Estate Conservation in two basic processes related to the settlement of the real estate situation. When accompanied by protests or disputes, the first is the general survey of land and the completion of real estate registration procedures. Real estate, each according to the nature of its specialization attempts to reconcile the parties to the dispute before resorting to these parties to the judiciary. On this subject we will know the scope of this reconciliation and its legal and administrative procedures.
لقد نظم المشرع الجزائري الصلح الإداري لدى مديرية الحفظ العقاري في عمليتين أساسيتين تتعلقان بتسوية وضعية العقارات؛ عندما يصاحب ذلك احتجاجات أو منازعات، الأولى عملية المسح العام للأراضي وإتمام إجراءات الترقيم العقاري، والثانية عملية التحقيق العقاري وتسليم السندات الملكية، حيث يبذل كل من المحافظ العقاري والمحقق العقاري كل حسب طبيعة تخصصه محاولات الصلح بين أطراف الخصومة قبل لجوء هاته الأطراف إلى القضاء. وفي موضوعنا هذا سنعرف نطاق هذا الصلح وإجراءاته القانونية والإدارية.
Keywords: الصلح الإداري -- الملكية العقارية -- تسوية النزاعات -- القوانين والتشريعات -- الجزائر